PENGARUH KUALITAS PELAYANAN DAN MUTU PRODUK TERHADAP KEPUASAN PELANGGAN DI SOGO BALI COLLECTION - Ira Fridawati (Majalah Ilmiah Widyacakra, 2019)
Along with the development of tourism today, especially in the Nusa Dua area, Sogo Bali Collection continues to improve service quality and quality of products sold to customers. On this basis the authors are interested in conducting a research entitled "The Influence of Service Quality and Product Quality on Customer Satisfaction at Sogo Bali Collection.The main problem is whether there is a partial and simultaneous influence between service quality and product quality on customer satisfaction at Sogo Bali Collection. The analysis technique used is Multiple Regression Analysis, Multiple Correlation Analysis, Determination, T Test and F Test with an error rate of 5%. From the results of the using the SPSS program, then the following results are obtained:There is a positive and significant partial effect between service quality (X1) on customer satisfaction (Y) and product quality (X2) on customer satisfaction (Y) at Sogo Bali Collection, this can be seen from the regression coefficient (b1) X1 positive value of 0.527 and t-test at the error rate (ἀ) 5% at 4.740> t-tab (0.05: 47) = 1.677 and the regression coefficient ( b2) X2 for 0.365 the results of the t-test at the level of error (ἀ) 5% at 3,052> t-tab (0.05: 47) = 1,677. Besides that there is a simultaneous and significant positive effect / together if service quality (X1) and product quality (X2) on customer satisfaction (Y) at Sogo Bali Collection giving a very strong contribution / influence of 98% and 2% again determined by other factors not discussed in this study; while the regression equation is Y = 2.686 + 0.527X1 + 0.365X2 with the value of F-test = 40,211> F-tab (0.05; 47) = 3.20 From the results of these studies it can be concluded that there is an influence of service quality and product quality on customer satisfaction at Sogo Bali Collection, management should do marketing simultaneously / together because it will be more instrumental and follow up on complaints from customers.